2009
DOI: 10.1007/s00264-009-0862-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of scaphoid nonunion with vascularised and nonvascularised dorsal bone grafting from the distal radius

Abstract: We conducted a prospective randomised study comparing the clinical, functional and radiographic results of 46 patients treated for scaphoid nonunion using a vascularised bone graft from the dorsal and distal aspect of the radius (group I), relative to 40 patients treated by means of a conventional non-vascularised bone graft from the distal radius (group II). Surgical findings included 30 sclerotic, poorly-vascularised scaphoids in group I versus 20 in group II. Bone fusion was achieved in 89.1% of group I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 24 publications
1
68
1
1
Order By: Relevance
“…A study that compared the use of vascularized versus conventional non-vascularized bone grafts from the distal dorsal radius concluded that vascularized bone gave a higher consolidation rate and superior functional results than the conventional non-vascularized procedure [18]. Patients which was agreement (correlation) of the results of pre-operative imaging tests and intra-operative and histological findings are marked (in bold) I increased radiodensity, N normal radiodensity In a clinical study, Bilic et al demonstrated that recombinant bone morphogenic protein (BMP) resulted in radiological and clinical repair of scaphoid non-unions with an avascular, necrotic proximal scaphoid after treatment with a vascularized pedicle bone graft [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that compared the use of vascularized versus conventional non-vascularized bone grafts from the distal dorsal radius concluded that vascularized bone gave a higher consolidation rate and superior functional results than the conventional non-vascularized procedure [18]. Patients which was agreement (correlation) of the results of pre-operative imaging tests and intra-operative and histological findings are marked (in bold) I increased radiodensity, N normal radiodensity In a clinical study, Bilic et al demonstrated that recombinant bone morphogenic protein (BMP) resulted in radiological and clinical repair of scaphoid non-unions with an avascular, necrotic proximal scaphoid after treatment with a vascularized pedicle bone graft [29].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic confirmation, however, is possible only with a histological examination [17]. It is important to have a pre-operative diagnosis of the vascular status of the non-united proximal segment of the scaphoid to plan the surgical approach [18].…”
Section: Introductionmentioning
confidence: 99%
“…Scaphoid fractures can go on to nonunion which can cause significant morbidity in terms of time off work and activities if not treated adequately [3,4]. Non-displaced (<1 mm displacement), stable fractures of the distal and middle third of the scaphoid can be treated conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies of fibular and iliac crest grafts to the mandible [20,35,41,50] and two studies of grafts from the iliac crest and radius to the scaphoid [7,37] that directly compared VBGs and NVBGs were identified and excluded from the search. These studies are inconclusive with respect to whether VBGs outperform NVBGs at increasing length, and are no basis to make clinical recommendations regarding long-bone and large-joint defects.…”
Section: Discussionmentioning
confidence: 99%